Public Rights and Private Remedies: Reflection on Enforcing Employment Standards through Grievance Arbitration - Shilton, Elizabeth (Canadian Labour and Employment Law Journal, 2017)
Some years ago, both Ontario and British Columbia amended their employment standards legislation to require employees in unionized workplaces to adjudicate their employment standards claims through their collective agree- ments. Unions at the time objected to the downloading of costs of public rights enforcement onto grievance arbitration - rightly, in the author's view, because grievance arbitration is designed to resolve disputes arising from private law generated by collective bargaining, not to enforce individual rights conferred by public law. By placing employment standards claims within the exclusive juris- diction of arbitrators, the amendments made those statutory rights part of the "bundle" that is subject to the compromises and tradeoffs inherent in collective agreement dispute resolution. The author acknowledges that there are compel- ling reasons to consolidate the adjudication of workplace disputes, including the potential for duplicative litigation, and the fact that private and public rights are closely intertwined in the modern workplace. What is needed, she suggests, is a custom-designed public tribunal, along the lines of a "labour court," with plenary jurisdiction to enforce both public and private rights, operating on prin- ciples that recognize society's interest in access to justice and equality before the law. She calls for further research to determine the impact of blending public and private rights enforcement systems on collective bargaining as an institution and on the welfare of unionized employees.